2014
DOI: 10.1002/adma.201400238
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Gold as Artificial Enzymes: Hidden Talents

Abstract: Creating artificial enzymes that mimic the complexity and function of natural systems has been a great challenge for the past two decades. In this Progress Report, the focus is on recently discovered "hidden talents" of gold nanomaterials in artificial enzymes, including mimicking of nuclease, esterase, silicatein, glucose oxidase, peroxidase, catalase, and superoxide dismutase. These unexpected enzyme-like activities can be ascribed to nano-gold itself or the functional groups present on surrounding monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
264
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(273 citation statements)
references
References 90 publications
3
264
0
Order By: Relevance
“…NP-based enzyme mimetics offer advantages in terms of cost, stability, ease of production and tenability of catalytic activity. Examples of NP systems with enzyme like activity include: nano-gold [16], ferromagnetic materials such as Fe 3 O 4 [17], Co 3 O 4 [18], sheet like-FeS nanostructures, CeO 2 [19], AgM (silver supported metallic nanoparticles), mesoporous silica encapsulated Pt [13]and metallic NPs supported graphene oxide [12,20]. Implementation of these materials in analytical and bioanalytical platforms could rouse development of a new generation of devices with significantly enhanced performances in stability and robustness compared to their enzyme counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…NP-based enzyme mimetics offer advantages in terms of cost, stability, ease of production and tenability of catalytic activity. Examples of NP systems with enzyme like activity include: nano-gold [16], ferromagnetic materials such as Fe 3 O 4 [17], Co 3 O 4 [18], sheet like-FeS nanostructures, CeO 2 [19], AgM (silver supported metallic nanoparticles), mesoporous silica encapsulated Pt [13]and metallic NPs supported graphene oxide [12,20]. Implementation of these materials in analytical and bioanalytical platforms could rouse development of a new generation of devices with significantly enhanced performances in stability and robustness compared to their enzyme counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[16] These enzyme mimetics have great value in practical applications, and therefore become a new frontier in inorganic, materials and analytical chemistry. [17][18][19] In previous studies, ceria nanoparticles (nanoceria) and nanoceria-supported materials have been reported to have multi-enzyme mimetic activities like those of superoxide oxidase, [20,21] catalase [22,23] and oxidase. [24,25] That means nanoceria have enzymatic activities to catalyze the scavenging of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 AuNPs have attracted the interest of scientists especially in the areas of 13 biosensing, 14 imaging, 15 and drug delivery. 2 Magnetic nanoparticles (MNPs) have generated considerable interest in the scientific world especially in the area of biomedicine and technology, particularly in magnetic storage media, 16 biosensing, 17,18 inks and paints, 19 drug delivery and contrast agents in magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%